Successful outcome in a perplexing case of Roberts uterus: a rare uterine anomaly, a rare case report with review of literature - Singh, Swati; Malik, Renuka; Gupta, Pooja; Ara, Anjum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Robert uterus is a rare Mullerian development anomaly with very few cases reports available. It presents with triad of morphologic features of - Blind hemi cavity with or without unilateral hematometra, contralateral unicornuate uterine cavity and normal uterine fundus with or without small external indentation. The major difficulty lies in making the diagnosis of Robert’s uterus. All the reported cases of Robert’s uterus have been managed differently according to patient’s complaints. A 25-year-old married female, resident of Agra presented to gynecology OPD of Dr RML Hospital and associated PGIMER in June 2013, with primary infertility and cyclical left sided dysmenorrhoea since menarche. Patient was consulting at her hometown Agra for 2 years and had an USG and MRI pelvis report of Feb. 2013 with her showing unicornuate uterus with rudimentary horn. Infertility investigations were done in our hospital. HSG report was of localized spill on right with left tubal block. Patient was posted for diagnostic hystero-laproscopy which was further followed by laprotomy, after which we could reach to a diagnosis of Robert uterus with non-communicating left cavity and with severe endometriosis. Patient needed a second hysteroscopy for lysis of septum and subsequently conceived with IVF. She delivered a healthy male baby of 2.65 kg by elective LSCS at 37 weeks with associated breech presentation with gestational hypertension with severe IHCP on 20 June 2019. Paediatric surgeons and gynecologists should be aware of this rare atypical obstructive Mullerian malformation and its management to avoid inappropriate management delays in these patients. A timely diagnosis and definite treatment have a great impact on future reproductive and endocrine function.